Alternative methodologies for sepiolite defibering - Lescano, Leticia (2014)
In this work, lyophilization and acid treatments were proposed as simple alternatives to defiber sepiolite samples, without affecting their length, in order to be applicable at industrial scale. Although it contains carbonates, themain remarkable feature of this clay mineral is its high crystalline development, reaching fiber lengths around 8 cm. Proposed alternatives were analyzed comparatively, evaluating mainly the defibering effect. The influence of lyophilization and acid treatments on sepiolite structure and purity was qualitatively studied based on mineral characterization, electronic and optical microscopy, X-ray diffraction and Fourier transform infrared spectroscopy. Results show that acid treatment allowed sepiolite purification by removing carbonates as well as the reduction of fiber length. Lyophilization demonstrated to be an effective defibering process that allowed obtaining individualized fiber from bundle disaggregation, without affecting sepiolite length and flexibility.